The Impact of Entrepreneurship Education on Entrepreneurship Competencies and Intentions - Hessel Oosterbeek; Mirjam van Praag; Auke IJsselstein (Tinbergen Institute, 2008)
This paper analyzes the impact of a leading entrepreneurship education program on college students' entrepreneurship competencies and intentions using an instrumental variables approach in a difference-in-differences framework. We exploit that the program was offered to students at one location of a school but not at another location of the same school. Location choice (and thereby treatment) is instrumented by the relative distance of locations to parents' place of residence. The results show that the program does not have the intended effects: the effect on students' self-assessed entrepreneurial skills is insignificant and the effect on the intention to become an entrepreneur is even significantly negative.
Keywords: A20; C31; H43; H75; I20; J24; L26; 330; Entrepreneurship education; program evaluation; entrepreneur competencies; entrepreneur intentions; Entrepreneurship-Ansatz; Führungskräfteentwicklung; Betriebswirtschaftsstudium; Wirkungsanalyse; Selbstständige; Niederlande